1999
DOI: 10.3109/13697139909025561
|View full text |Cite
|
Sign up to set email alerts
|

Climacteric modifications in body weight and fat tissue distribution

Abstract: Climacteric changes rather than the aging process are relevant for prediction of body weight and fat distribution, especially for perimenopausal and postmenopausal women, who show a shift to a central, android fat distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 11 publications
0
43
1
6
Order By: Relevance
“…This finding is consistent with the low serum levels of E 2 found in these patients. Sex hormones have an important impact on body fat distribution and there is evidence, at least for women, that a fall in E 2 -as observed during the menopause -is associated with a more central body fat distribution (35,36). However, conclusions should be drawn with caution on the basis of the present findings, since the DEXA technique does not allow the metabolically important differentiation between visceral and subcutaneous fat mass.…”
Section: Discussioncontrasting
confidence: 44%
“…This finding is consistent with the low serum levels of E 2 found in these patients. Sex hormones have an important impact on body fat distribution and there is evidence, at least for women, that a fall in E 2 -as observed during the menopause -is associated with a more central body fat distribution (35,36). However, conclusions should be drawn with caution on the basis of the present findings, since the DEXA technique does not allow the metabolically important differentiation between visceral and subcutaneous fat mass.…”
Section: Discussioncontrasting
confidence: 44%
“…This indicates a natural (normal) change in body fat distribution of middle-aged and older women. 5 In contrast, results of the GG genotype revealed that FM and waist size were inversely associated with age. Consequently, our data suggest that (1) middle-aged women with the GG genotype presented with a larger FM and waist, and (2) older women with the GG genotype presented with a smaller FM and waist, compared with the AA genotype, despite the observation in the middle-aged women (see Table 3).…”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3] Though, in general, upper-body or android-type 4 obesity, with a large waist or WHR, is more frequently observed in men compared with women, this obesity phenotype is also observed fairly often in postmenopausal women. 5 This is because estrogen deficiency during the normal menopausal transition accelerates the selective deposition of intra-abdominal fat. 6 With respect to estrogen's association to body fat distribution, several authors [6][7][8][9][10] have reported that estrogen hormone replacement therapy had desirable effects on body fat distribution in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…In animal experiments it was shown that a lack of estrogen causes an increase of body fat resulting in obesity (Danilovich, et al, 2000, Heine, et al, 2000 and hypercholesterolemia (Hewitt, et al, 2003, Jones, et al, 2000. The increase in body fat weight combined to a changed distribution of fat depots to a more central android distribution can be observed in postmenopausal women as well (Gambacciani, et al, 1999, Gambacciani, et al, 2001, Gambacciani, et al, 1997. These effects might be mediated by the ERβ (Liang, et al, 2002) but research with estrogen receptor α knock out mice (αERKO) points more towards an ameliorating effect of the ERβ (Naaz, et al, 2002).…”
Section: Estrogen Estrogen Estrogen Estrogen Estrogenmentioning
confidence: 96%